Pengaruh Media Papan Hitung Polinomial (PHP) terhadap Hasil Belajar Siswa ditinjau dari Uji Wilcoxon - Handini, Wheni Putri; Fikriyah, Alif Zakiyatul; Nurwiani (Universitas Pendidikan Mandalika (UNDIKMA), 2025)
Learning media serve as tools that connect teachers and students in the learning process. Previous studies have shown that learning media allow students to participate directly in learning activities. Therefore, the Polynomial Counting Board (PHP) can be used as an instructional medium for performing polynomial operations, enabling students to engage more actively and accurately during the learning process. Through the use of PHP, students are expected to be more careful when solving polynomial operation problems and more involved in classroom activities. This study applies the Wilcoxon test to examine the effect of PHP on students’ learning outcomes, a test that has not been previously used in the development of similar learning media. The research uses a quantitative approach with an experimental method and a One-Group Pretest–Posttest Design. The sample consists of students from class XI Science 1 at MA Sains Tebuireng Putri Kesamben. The observed variables include the independent variable (PHP media) and the dependent variable (learning outcomes). Data were collected using pretest and posttest instruments. The analysis involved the Shapiro–Wilk normality test and a nonparametric statistical analysis using the Wilcoxon test. The results of data analysis and hypothesis testing through the Wilcoxon Signed Rank Test show an Asymp. Sig (2-tailed) value of 0.001, which is lower than the significance level α = 0.05. This indicates a significant difference (H₀ rejected, H₁ accepted) and demonstrates that the PHP learning media has a positive effect on students’ learning outcomes, with an effect size of 0.67.